Detection and Correction of Under-/Overexposed Optical Soundtracks by Coupling Image and Audio Signal Processing. (14th October 2008) - Taquet Taquet, Jonathan Jonathan; Besserer Besserer, Bernard Bernard; Hassaine Hassaine, Abdelali Abdelali; Decenciere Decenciere, Etienne Etienne
Abstract : Film restoration using image processing, has been an active research field during the last years. However, the restoration of the soundtrack has been mainly performed in the sound domain, using signal processing methods, despite the fact that it is recorded as a continuous image between the images of the film and the perforations. While the very few published approaches focus on removing dust particles or concealing larger corrupted areas, no published works are devoted to the restoration of soundtracks degraded by substantial underexposure or overexposure. Digital restoration of optical soundtracks is an unexploited application field and, besides, scientifically rich, because it allows mixing both image and signal processing approaches. After introducing the principles of optical soundtrack recording and playback, this contribution focuses on our first approaches to detect and cancel the effects of under and overexposure. We intentionally choose to get a quantification of the effect of bad exposure in the 1D audio signal domain instead of 2D image domain. Our measurement is sent as feedback value to an image processing stage where the correction takes place, building up a "digital image and audio signal" closed loop processing. The approach is validated on both simulated alterations and real data.